Germinal Center B Cells are Uniquely Targeted by Antibody-Suppressor CXCR5+CD8+ T Cells - Jason M. Zimmerer, PhD; Sachi Chaudhari, BS; Kavya Koneru, BS; Jing L. Han, MD, PhD; Mahmoud Abdel-Rasoul, MA; Hope Uwase, MA; Tai Yi, MD; Christopher K. Breuer, MD; Ginny L. Bumgardner, MD, PhD (Transplantation Direct)
Background. Alloprimed antibody-suppressor CXCR5+CD8+ T cells (CD8+ TAb-supp cells) downregulate alloantibody production, mediate cytotoxicity of IgG+ B cells, and prolong allograft survival. The purpose of this investigation was to determine which immune-cell subsets are susceptible to CD8+ TAb-supp cell–mediated cytotoxicity or noncytotoxic suppression. Methods. Alloprimed immune-cell subsets were evaluated for susceptibility to CD8+ TAb-supp cell–mediated in vitro cytotoxicity and/or suppression of intracellular cytokine expression. In vivo CD8-mediated cytotoxicity to wild-type germinal center (GC) B cells or wild-type CD4+ T follicular helper cells (TFH cells) was assessed in RAG1 knockout mice. The impact of in vivo adoptive transfer of CD8+ TAb-supp cells into hepatocyte or kidney transplant recipients on the quantity of lymphoid immune-cell subsets was assessed. Results. CD8+ TAb-supp cells mediated allospecific cytotoxicity to alloprimed GC B cells but not alloprimed extrafollicular plasmablasts, marginal zone B cells, follicular B cells, or plasma cells. CD8+ TAb-supp cells did not mediate cytotoxicity to alloprimed dendritic cells, macrophages, CD4+ TFH cells, CD4+ T follicular regulatory cells, or CD4+ regulatory T cell. CD8+ TAb-supp cells did not suppress CD4+ TFH cell, T follicular regulatory cell, or regulatory T-cell cytokine expression. Adoptive transfer of CD8+ TAb-supp cells into hepatocyte or kidney transplant recipients reduced alloantibody production and the quantity of GC B cells, TFH cells, and plasma cells (but not other B-cell, T-cell, or antigen-presenting cell subsets). The reduction of TFH-cell quantity was dependent on CD8+ TAb-supp cell–mediated major histocompatibility complex-I-dependent cytotoxic killing of GC B cells. Conclusions. The primary targets of CD8+ TAb-supp cells are GC B cells with downstream reduction of TFH and plasma cells.